2021
DOI: 10.3389/fphys.2021.758859
|View full text |Cite
|
Sign up to set email alerts
|

Tenebrio molitor Spätzle 1b Is Required to Confer Antibacterial Defense Against Gram-Negative Bacteria by Regulation of Antimicrobial Peptides

Abstract: Innate immunity is the ultimate line of defense against invading pathogens in insects. Unlike in the mammalian model, in the insect model, invading pathogens are recognized by extracellular receptors, which activate the Toll signaling pathway through an extracellular serine protease cascade. In the Toll-NF-κB pathway, the extracellular spätzle protein acts as a downstream ligand for Toll receptors in insects. In this study, we identified a novel Spätzle isoform (TmSpz1b) from RNA sequencing database of Tenebri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…This protein is a zymogen and is cleaved to its mature form by a chain of serine protease activation, following pathogen recognition by PRRs (24,57). The immunological roles of Spz isoforms (Spz1b, Spz-like, Spz4, Spz5, and Spz6) in T. molitor have been investigated using RNAi (58)(59)(60)(61)(62). Among them, TmSpz1b, TmSpz-like, and TmSpz5 showed anti-Gramnegative bacterial (E. coli) activity (58,61,62).…”
Section: Cross-regulation Of Imd and Toll Pathways In T Molitormentioning
confidence: 99%
See 2 more Smart Citations
“…This protein is a zymogen and is cleaved to its mature form by a chain of serine protease activation, following pathogen recognition by PRRs (24,57). The immunological roles of Spz isoforms (Spz1b, Spz-like, Spz4, Spz5, and Spz6) in T. molitor have been investigated using RNAi (58)(59)(60)(61)(62). Among them, TmSpz1b, TmSpz-like, and TmSpz5 showed anti-Gramnegative bacterial (E. coli) activity (58,61,62).…”
Section: Cross-regulation Of Imd and Toll Pathways In T Molitormentioning
confidence: 99%
“…The immunological roles of Spz isoforms (Spz1b, Spz-like, Spz4, Spz5, and Spz6) in T. molitor have been investigated using RNAi (58)(59)(60)(61)(62). Among them, TmSpz1b, TmSpz-like, and TmSpz5 showed anti-Gramnegative bacterial (E. coli) activity (58,61,62). silencing of TmSpz1b downregulated the expression of TmDorX1 and TmRel in the immune organs (58).…”
Section: Cross-regulation Of Imd and Toll Pathways In T Molitormentioning
confidence: 99%
See 1 more Smart Citation
“…Another Spz isoform, Tm-Spz 1b (Genbank MZ708791), was identified and functionally characterised by Bae et al in 2021 [ 101 ]. Developmental and tissue-specific expression profiles established that Tm-Spz1b was mainly expressed in adult hemocytes and the late larval stage.…”
Section: T Molitor Gene Expression Studies Related To Microb...mentioning
confidence: 99%
“…AMP-coding genes of RNAi larvae hemocytes and fat were downregulated in response to the E. coli challenge and Tm-DorX2 transcripts. Thus, these results suggested that Tm-Spz1b was required to confer antibacterial defence against Gram-negative bacteria but not against Gram-positive and fungal infections [ 101 ].…”
Section: T Molitor Gene Expression Studies Related To Microb...mentioning
confidence: 99%